Use of Lactobacillus plantarum and Propionibacterium freudenreichii ssp. Shermanii as inoculants in corn silage fermentation - Abdul Rahman, Norafizah (2017)
Bacterial inoculant as feed additives have been shown to be beneficial in silage fermentation in many parts of the world. However, there is still not much evidence of the use of bacterial additives in Malaysia and the impact of using them to produce quality feed for ruminant industry is rarely documented. Thus, this study was conducted to determine the effectiveness of using two bacterial additives for corn silage fermentation in Malaysia. The two bacterial species used in this study were Lactobacillus plantarum (B1) and Propionibacterium freudenreichii (B2). These bacteria were applied singly and as a mixture of both bacteria (B3).